I starten var det Hofteregisteret - så ble vi flere - Ove Furnes; Jan-Erik Gjertsen; Eivind Inderhaug; Trude Gundersen; Anne Marie Fenstad; Stein Atle Lie; Geir Hallan (Norsk Forening for Epidemiologi, 2023)
-